Al yugo y obediencia de la Iglesia y su Majestad : acercamiento al Demócrates II de Juan Ginés de Sepúlveda (2015)
ABSTRACT: The Tratado de las justas causas de la guerra contra los indios is perhaps the most controversial text written by Juan Ginés de Sepúlveda. It was meant to reply the critics about the papal concession on the New World. This book was forbidden by the Inquisition, both, author and dialogue, were indicted of being proslavery and was printed only 300 years later on 1892. However, studying Sepulveda’s personal life, his social status and education gives a reassessment to his book and legacy.